Cultural industry development from entrepreneurship under the background of rural revitalization strategy - Gao, Jing (Frontiers in Psychology, 2022)
The implementation of the rural revitalization strategy can effectively inherit the excellent traditional Chinese culture and facilitate the comprehensive development of the cultural industry. At present, China is promoting the transformation and upgrading of its industrial structure. The criterion for measuring the “cultural soft power” of a country or region is the competitiveness of its cultural industry. The cultural industry has grown rapidly in recent years, and the overall economic benefits of the industry have also improved, effectively alleviating the employment pressure across the country. However, there are still many problems. How to accurately measure the level of competitiveness of the regional cultural industry and enhance its competitiveness is the first problem in the development of the cultural industry. It finds out the main factors that affect the competitiveness of the cultural industry in the context of rural revitalization strategy using the relevant theories of cultural industry and industrial competitiveness. Besides, the evaluation index system of cultural industry competitiveness is constructed from the perspective of the system. The projection pursuit model and data envelopment analysis model are established based on the genetic algorithm. The model is used to carry out empirical research on the competitiveness level of cultural industry in a region, and conclusions are drawn. The average projected value of the base competitiveness in the region exceeds 0.8. The average projected value of dominant competitiveness exceeds 0.7. The average projected value of potential competitiveness exceeds 1.1. The research proposes corresponding suggestions for the problems in the current growth of the cultural industry in this region through the competitiveness of this region and the level of other areas. It can also provide some help for the in-depth study of the Chinese cultural industry.